Trust in the Justice System: Internet Survey after Introducing Mixed Tribunal System in Japan - Masahiro Fujita; Nahoko Hayashi; Syûgo Hotta (Oñati Socio-Legal Series)
People obey the law because they think it is legitimate, and trust is the key that makes the legal system work. The jury system promotes public trust in the justice system through lay people’s participation. In the current study, the authors investigated the relationships between citizens’ trust in the social system, general trust, feelings of legitimacy for the justice system, and other social variables. The survey was conducted in March 2013 through the Internet and 1,609 Japanese people responded. With these data, the authors tested relational models of the factors that determine citizens’ trust in the legal system, and relationships among these factors.